ACCOUNTING FOR EXCHANGE DIFFERENCES ON FOREIGN CURRENCY LIABILITIES OF ENTERPRISES UNDER MARTIAL LAW - Fatenok-Thachuk, Alla; Lakhtiuk, Tetiana (Current Problems of Sustainable Development, 2026)
The ongoing full-scale invasion of Ukraine has fundamentally transformed the economic landscape, necessitating rapid adaptations in currency regulation and financial reporting. The evolution of the National Bank of Ukraine’s (NBU) policies – transitioning from a fixed exchange rate in 2022 to managed flexibility in 2024–2026 – has created significant challenges for accounting practitioners, requiring continuous adaptation of accounting policies and a high level of professional judgment in non-standard situations. This article addresses the critical need to refine the accounting and analytical support for foreign currency transactions, focusing on the recognition and measurement of exchange rate differences under extreme volatility and regulatory constraints. The study examines the classification of foreign currency liabilities into monetary and non-monetary items in accordance with NAS 21 and IAS 21, and defines the procedures for their remeasurement at the balance sheet date and the recognition of exchange differences in profit or loss. Special attention is paid to the regulatory framework governing foreign currency settlements under martial law, including NBU resolutions introducing restrictions on currency transfers, dividend repatriation, and settlements with non-residents. The article analyses the accounting implications of the one-time hryvnia devaluation in July 2022 and the subsequent transition to a managed flexibility regime, both of which generated substantial exchange losses for enterprises with significant foreign currency liabilities. The study identifies key practical challenges specific to wartime conditions: the accounting treatment of frozen obligations subject to NBU-imposed moratoria, force majeure circumstances confirmed by the Ukrainian Chamber of Commerce, loss of primary documents in temporarily occupied territories, and the classification of foreign aid as monetary or non-monetary liabilities. It is argued that the absence of dedicated methodological guidance for accounting under armed conflict conditions forces practitioners to rely solely on professional judgment, thereby increasing the risk of material misstatements in financial reporting. The article concludes that the development of specific regulatory recommendations by the Ministry of Finance of Ukraine, combined with the gradual convergence of NAS 21 with IAS 21, is essential for enhancing the reliability of financial statements and strengthening the economic security of Ukrainian enterprises in the context of post-war recovery and European integration.